The Impact of Commodity Prices, Interest Rate and Exchange Rate on Stock Market Performance in South Africa - Mudau, Phathutshedzo (University of the Witwatersrand, Johannesburg, 2023)
The relationship between commodity prices and the stock market has been an important focus in literature. This relationship is especially important for a rich mineral resource country with an export-based economy like South Africa. Fluctuating commodity prices create significant business challenges, impacting production costs,product pricing and profitability. Understanding factors that affect the stock market performance becomes important, since the performance of the stock market is associated with the economic condition. This study examined the sensitivity of stock market performance to fluctuations in commodity prices and macroeconomic factors, using monthly data that spans from January 2005 to December 2020. Crude oil and platinum were selected as commodities while interest rate and exchange rate were selected as macroeconomic factors for this study. Ordinary Least Square (OLS) regression method was deployed, together with quantile regression, in this study to achieve the objective. The resulting OLS regression model was also tested for goodness of fit and the residuals tested to validate the model. It was found that commodity price fluctuations affect stock market performance positively and macroeconomic factors affect it negatively. An increase in platinum price caused an increase in the stock market performance. This reflects the importance of palatinum as one of the most produced and exported minerals in South Africa. Crude oil price fluctuations had a positive impact on the stock market performance. The positive impact could be due to South Africa’s trade balance or the source of the crude oil price shock. Exchange rate showed the highest impact on the performance of the stock market. Cheaper imports shift demand from locally produced goods in favour of import, affecting their profitability. Interest rate had a negative but insignificant impact on stock market performance.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investments, Johannesburg, 2023
Keywords: Stock market; Interest rate; Exchange rate; Crude oil; Platinum; SDG-8: Decent work and economic growth